Unlocking Human Potential: A Reflection on Genesis 11:6 - Robijaona Rahelivololoniaina Baholy (Britain International for Academic Research (BIAR) Publisher, 2024)
Genesis 11:6 illuminates the intertwining realms of human potential and divine purpose, extolling the limitless power when united. This timeless summons encourages noble pursuits in reverence to the Creator. Employing a methodology bridging the Bible and the Internet, ingenious narratives in both Testaments exemplify human prowess. Online, the evolution of technology and social networks manifests breakthroughs, including the realm of artificial intelligence. This progress aligns with scientific feats like cloning, in vitro babies, and transformative plastic surgery. Yet, amidst this expansive landscape, limitations persist. Societal constraints, environmental factors, self-imposed boundaries, and the overarching authority of the divine collectively circumscribe human endeavors. This exploration underscores the delicate interplay between human ingenuity and divine order, prompting contemplation on ethical dimensions and the intricate balance inherent in the multifaceted journey of human existence.